Elaboración de un manual de gestión integral de desechos sólidos en el mercado mayorista del cantón mejía provincia de pichincha, período 2019-2020. - Jácome Pila, Paola Lizeth (2020)
Research work developed at wholesale market of Mejía Canton, in different areas of commercial stores. The used methodology to get information as a basis to verify the regarding situation of solid waste management from its origin, storage, collection, handling, transport and final disposal was data collecting. Then the solid waste characterization was carried out in order to determine the quantity and type generated in the market. Later the analysis of the results and finally the elaboration of integral management manual of solid wastes were made. Through the obtained results during the 36 consecutive days of sampling, the Production per capita is 1.11 (kg / hab / day) and the percentages for each type of residue are 45.8% in fruit and vegetables; food scraps 23.9%; paper 13.5%; 0.1% glass; cardboard 7.9%; plastic 8.9%. Regarding the characterization, it was determined that the most generated residues are with organic characteristics (fruit, legumes, food scraps) with a total of 69.7%, followed by inorganic waste (paper, glass, plastic cardboard) with 30.3% according to the data collected, the days that generate the most solid waste are Saturdays with 3907 K, and Sundays with 5173 Kg, respectively. An average percentage of production on Thursdays with 3237 Kg, and finally an average low on Mondays with 2639 Kg, Tuesday with 2508kg, and Fridays with a value of 2490 Kg. The Integrated Management Manual of Solid Waste of Mejia Canton Wholesale market, will be a guide for waste management from the source to its final disposal.